Second Chances Academy: Alternative School or Pathway to Prison?. (March 2016) - Horsford, Sonya Douglass; Powell, Keyona L.
This case considers the leadership challenge facing district officials in a mid-sized urban–suburban school district receiving negative media coverage for the overrepresentation of poor, Black, and Latino males in its alternative high school, Second Chances Academy. Many of its students also qualify for special education and English learner services. Local civil rights leaders have expressed moral outrage over the school's abysmal graduation rate, describing it as a "pit stop" along the school-to-prison pipeline. Now that the third principal in 2 years has resigned, the district superintendent must not only manage public criticism and find the right person to lead Second Chances Academy but also confront the socially unjust practices embedded in his district's alternative education program.